Competência leitora dos textos multimodais : interagindo com objetos digitais de aprendizagem - Santos, Sandra Virgínia Correia de Andrade (2015)
Starting with an interactive and reflective perspective, this study aims to develop the reader competence before multimodal elements present in a contemporary textual composition, making effective practices of visual reading able to improve the students language skills . For this research, it was adopted as the scientific method Case Study with qualitative and quantitative approach, with the empirical field EMEF Iraildes Padilha Carvalho in the town of Tobias Barreto-SE. As a collection instrument was held an observation and a questionnaire. The research is based on the Grammar of Visual Design Kress and Van Leween (1996), which promotes the view that the visual elements present have a specific and significant architecture. As theoretical contribution was used also for studies of Rojo and Moura (2013), Marcuschi (2011), Bakhtin (2011), Tarouco (2003) and Dionysus (2011) among others. It was being that visual reading assumption is little explored in the classroom as well as the necessity of including the interactive and dynamic technology in pedagogical practices, elaborated a Digital Object Learning (ODA) for using with students during the development of research. In this context, it was decided to Nightmare magazine cover as the corpus to be investigated, from which were planned strategies and resources to be applied in the classroom. After the whole process of research, the results showed that students little explored the visual elements present in the texts, in spite of the fact that the unilateral perception of the images and other visual elements are for illustration only. It also has proven itself to digital resources enable the exploration and expansion of visual reading, bringing the student a dynamic and meaningful learning.